A feasibility study of a home-ownership program for the public housing of Hong Kong - Yeh, Anthony Gar-on; Angel, Shlomo; Goede, J.H. de; Hwang, M.C.; Government of Canada (Bangkok : Asian Institute of Technology, 1976)
Hong Kong is one of the few large cities in any part of the Third World which has responded to its housing problems by large scale estate construction of public units. Many studies have been done on the housing demand, housing standard, residential density and environment of the public estates. However, no studies has been made on the important aspect of "home-ownership" of public housing by the people. In October, 1972, the government of Hong Kong announced the ambitious 10 Year Housing Programme which aimed to build public housing on such a scale that there will be permanent, self-contained accommodation, in a reasonable environment, for virtually everyone in Hong Kong. Since the 10 Year Housing Programme will greatly influence the livelihood of the majority of Hong Kong citizens, it is very important for the government of Hong Kong at this early stage of the 10 Year Housing Programme to review the past public housing policy and to formulate a long-range, appropriate and more satisfactory public housing program and policy. The main theme of the study is to provide information on the basis of which the government can evaluate the possibility of a home-ownership program for its public housing tenants, so as to incorporate such a program as part of its long term public housing policy. Attempts are also made to identify the determinants of home-ownership preferences, Understanding of the determinants of home-ownership preferences could help in the future estimation of home-ownership demand and the characteristics of potential home-buyers. The approach of the study is three-folded:- demand side (user-oriented), supply side (supplier-oriented) and the public (community-oriented). In the supply side, the housing officials of the Hong Kong Housing Authority and Hong Kong Housing Society are interviewed informally about their attitudes and constraints towards the public home-ownership program. In the community oriented study, the opinions of the society leaders towards such program are solicited, In the demand side, public tenants are interviewed with a structure questionnaire. Questions are set to reveal the preferences and abilities of the public tenants towards the public home-ownership policy. A home-ownership model was constructed to differentiate between potential buyers and non-buyers. Potential buyers as defined in the study are those who both have the ability and interested in buying public housing in the future. The ability to own is a relative concept and therefore is very difficult to estimate. greatly influenced by the house price and mortgage terms. It is Attempts are made in the study to measure the ability to own in four different methods. The finding shows that there are little technical and financial constraints in restricting the supplier (Housing Authority) in providing public housing for sale to the public. The main dispute is on the amount of subsidies that should be given to the future buyers of home-ownership scheme. Land Price, resale control, allocation of buyers, management and maintenance of estates for sale are details that awaits to be settled before the home-ownership program can be envisaged. Most community leaders favour the idea of public home-ownership program. However, they think that only new units should be sold because of the foreseeable management program after the sale of the old existing units. The majority thinks that the public home-ownership program will bring more benefits than negative effects to Hong Kong. Rules and regulations, the control of reselling, the problem of allocation and initial capital are seen as the main difficulties in future planning and implementation of a home-ownership program for Hong Kong. In the demand side, the preference and demand for two main method of home-ownership scheme are investigated. The two methods are namely easy government mortgage loan and selling of public flats to tenants. The study shows that because of the extremely expensive private house price, only as little as 27.4 percent of the public tenants said that they were interested in borrowing easy government mortgage loan, whereas 67.5 percent of them said that they were interested in owning public housing units. The main reason for not borrowing easy mortgage loan or buying public housing is financial reason. However, the second most important reason is that the public tenants are satisfied with their present residential environment of the public housing. Although 67.9 percent of the public tenants are interested in becoming public home-owners, only 33.9 percent of them have the ability to own public housing under very favourable mortgage terms and house price. The comparison of estimation methods of ability to own public housing shows that the users preference method is more reliable and realistic than the other 3methods. The determinants of home-ownership study shows that household expenditure is not p~0portional to household income. Care has to be taken in using household income as indicators for housing expenditures and demands. The study shows that. it is community acceptable, supplier capable, and in the demands by tenants for Hong Kong to Launch a public home-ownership program. The conclusions and recommendations as derived from the study could provide a framework and guideline for the government of Hong Kong in Planning and implementing its future home-ownership program.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science of the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Sc.) - Asian Institute of Technology, 1976
Keywords: Public housing -- Hongkong